Chinese motorbikes versus bush taxis - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2006)
In Cameroon and the forested areas of Guinea, the advent of cheap Chinese motorbikes is opening up remote villages and stimulating trade...